1998
DOI: 10.1002/(sici)1521-4141(199803)28:03<1089::aid-immu1089>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of amplitude and direction ofin vivo immune responses by co-administration of cytokine gene expression cassettes with DNA immunogens

Abstract: Immunization with nucleic acids has been shown to induce both antigen-specific cellular and humoral immune responses in vivo. We hypothesize that immunization with DNA could be enhanced by directing specific immune responses induced by the vaccine based on the differential correlates of protection known for a particular pathogen. Recently we and others reported that specific immune responses generated by DNA vaccine could be modulated by co-delivery of gene expression cassettes encoding for IL-12, granulocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(131 citation statements)
references
References 50 publications
(67 reference statements)
2
128
1
Order By: Relevance
“…Successful DNA immunization with IL-4 as a molecular adjuvant to enhance Th2 type of immune responses to different immunogens has been previously reported [20,21,[35][36][37][38][39]. However, to our knowledge no one examined whether anti-IL-4 antibody production is generated when IL-4 is used as a fusion protein with the immunogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful DNA immunization with IL-4 as a molecular adjuvant to enhance Th2 type of immune responses to different immunogens has been previously reported [20,21,[35][36][37][38][39]. However, to our knowledge no one examined whether anti-IL-4 antibody production is generated when IL-4 is used as a fusion protein with the immunogen.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has also been reported that co-administration of IL-4 cytokine gene along with a gene, encoding foreign or "self" antigens, caused the immune response to be driven toward a more Th2-like phenotype [20,21,[35][36][37][38][39]. Here we describe a novel chimeric DNA minigene encoding A g fused with mouse IL-4.…”
Section: Introductionmentioning
confidence: 99%
“…To seek an approach to increase the efficacy of the pE DNA vaccine, we tested the use of cytokines as immunological adjuvants. It has been previously demonstrated that the magnitude and nature of the immune responses to DNA vaccines can be regulated by coadministration of a broad panel of cytokine genes (25)(26)(27). Among these cytokine genes, the IL-12 gene promotes Th1 responses and cell-mediated immunity, and the IL-4 gene favors Th2 cell development and production of Abs.…”
Section: Suppression Of Immune Response and Protective Immunity To A mentioning
confidence: 99%
“…In some reports, the use of cytokine genes brought significant elevation in CTL activities against the antigens. [14][15][16][17]19,21 The results strongly suggest the potential usefulness of the cytokine gene delivery as molecular adjuvants.…”
Section: Introductionmentioning
confidence: 96%
“…pDNAs encoding interferon (IFN)-g, 14 IL-2, [15][16][17] IL-12, 9,14,[17][18][19][20] 21 IL-18 9,22 and granulocyte-macrophage colony-stimulating factor (GM-CSF) 15,17,19 have been shown to enhance Th1 immune responses triggered by a pDNA vaccine against human immunodeficiency (HIV) virus, [15][16][17]19,21 hepatitis B virus, 14 mycobacterium 20 and HSV, 9,18,22 although the humoral response was elevated 9,[14][15][16][17]19 or downmodulated, 15,18,20,21 depending on the cytokines and antigens employed. In some reports, the use of cytokine genes brought significant elevation in CTL activities against the antigens.…”
Section: Introductionmentioning
confidence: 99%